Spectroscopic characterization of a novel 2×[4Fe–4S] ferredoxin isolated from Desulfovibrio desulfuricans ATCC 27774 - Rodrigues, Pedro (2014)
A novel iron /sulfur containing protein, a ferredoxin (Fd), was purified to homogeneity from the extract of Desulfovibrio desulfuricans American type culture collection (ATCC) 27774. The purified protein is a 13.4 kDa homodimer with a polypeptide chain of 60 amino acids residues, containing eight cysteines that coordinate two [4Fe /4S] clusters. The protein is shown to be air sensitive and cluster conversions take place. We structurally characterize a redox state that contains two [4Fe /4S] cores. 1D and 2D 1H NMR studies are reported on form containing the clusters in the oxidized state. Based on the nuclear Overhauser effect (NOE), relaxation measurements and comparison of the present data with the available spectra of the analogous 8Fe Fds, the cluster ligands were specifically assigned to the eight-cysteinyl residues.